Kazimierz Wielki jako reformator i człowiek - Skodlarski, Janusz (Annales. Etyka w Życiu Gospodarczym, 2008)
Endowed with all the traits of an outstanding monarch and creator of his state, King Kazimierz III (also known as the Great) appears one of the greatest figures in the history of Poland. It was him who laid out the legal and political foundation of the modern state. He initiated legislative, administrative, economic, military and cultural reforms which became the source of the power of the Jagiellonian dynasty. However, apart from the above mentioned virtues, Kazimierz Wielki had a number of vices and weaknesses. He tended to be irritable and bad-tempered. He overly appreciated jewels and luxury. What is more, he was promiscuous and overindulged in drinking and eating.